2018
DOI: 10.3201/eid2407.171937
|View full text |Cite
|
Sign up to set email alerts
|

Influenza D Virus Circulation in Cattle and Swine, Luxembourg, 2012–2016

Abstract: We detected antibodies against influenza D in 80.2% of the cattle sampled in Luxembourg in 2016, suggesting widespread virus circulation throughout the country. In swine, seroprevalence of influenza D was low but increased from 0% to 5.9% from 2012 to 2014–2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 9 publications
7
90
1
2
Order By: Relevance
“…To our knowledge, this is the first report of identification of IDV in western Canada. IDV was initially identified in swine in the United States, and then was found to be prevalent in cattle of the United States, Luxembourg, Ireland, France, Japan and China (Flynn et al, ; Mekata et al, ; Snoeck et al, ; Su, Fu, Li, Kerlin, & Veit, ). IDV may be an emerging pathogen in Canadian cattle; or, on the other hand, the lack of Canadian reports before may be due to the unavailability of a diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of identification of IDV in western Canada. IDV was initially identified in swine in the United States, and then was found to be prevalent in cattle of the United States, Luxembourg, Ireland, France, Japan and China (Flynn et al, ; Mekata et al, ; Snoeck et al, ; Su, Fu, Li, Kerlin, & Veit, ). IDV may be an emerging pathogen in Canadian cattle; or, on the other hand, the lack of Canadian reports before may be due to the unavailability of a diagnostic assay.…”
Section: Discussionmentioning
confidence: 99%
“…No efforts have been undertaken to gather knowledge on putative IBV and ICV infections in European swine although sporadic incidents had been reported in the past . IDV likewise was not a target of investigation programmes, with the exception of some IDV screening in Italian swine, showing a virus prevalence of 2% and a seroprevalence of 11.7%, and serological studies in Luxembourgian swine showing an increasing seroprevalence from 0 to 5.9% in the years 2012‐2015 …”
Section: Discussionmentioning
confidence: 99%
“…However, the low genetic homology and lack of antibody cross‐reactivity to ICV led to its designation as a new influenza virus type, tentatively named influenza D virus (IDV) . To this day, it was found in swine but more frequently in cattle showing mild respiratory disease suggesting cattle may be the domestic reservoir species for IDV . No human cases were discovered thus far though antibodies for IDV were found in people with close contact to cattle and swine, and in vitro studies demonstrated the ability of the virus to grow in human‐derived cells …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations